En torno a la confianza - Lozano, Jorge (CIC. Cuadernos de Información y Comunicación, 2003)
The author of this text explores the concept of Confidence/Trust in a rich range of philosophical sources, as well as referenees from literary, socialthought or communication theories, showing its essential nature. The concept of Confidence appears inside the interaction processes as well as in systemic social structures, as a presupposition of their respective efficiency and as the motor strength of communicative acts of every level. Showing us how Confidence has been an essential subject between great human thinkers, the author gathers. between otber. the linking power that Simmel pointed in Trust or the cognitive and emotive weights which confidence develops in human intercourses.
Keywords: Confiance; Communication; Confiance et Philosophie; Confiance et Littérature; Confiance et Théorie Sociale; Interaction et confiance; Systéme Social et confiance; Négociation et conliance; Georg Simmel